Stalking e tutela penal : soluções de lege lata e de lege ferenda no ordenamento jurídico brasileiro - Flores, Carlos Pereira Thompson (2016)
The following work, fulfilled in the Postgraduate Program, in Criminal Science at PUCRS, is part of the research line of legal and criminal contemporary systems, aiming to assess the need for the Brazilian Criminal Code to introduce a specific article aimed to punish the conducts that substantiate Stalking. Firstly, we have prepared an introduction to the topic of Stalking, as well as to the studies on the subject carried out at international level. In the second part, we analyzed the legal systems in the European Union and United States that have choosen to include in their legislation a specific anti-Stalking article. We concluded our work by analyzing the political-criminal brazilian legal system de lege lata and de lege ferenda and assessing the hypothetical inclusion of a specific legal category in our Criminal Code.